Towards freedom: open questions (Balthazar, 2022)
Contemporary literature and cinema have shown in recent years a resurgence of a theme dear to Romanticism: the journey to “wild lands” as an escape from an alienated existence, a conformist life, and a society of undifferentiated individuals. This work presents the analysis of this theme, already present in authors like Goethe and the explorers of the 18th century, in four highly successful literary works. Firstly, Heroes of the Frontier by Dave Eggers. The central concept of the work is “rupture”, symbolically present in every passage of the novel and linked to the idea of freedom and escape. The second novel analyzed is the famous Into the Wild by Krakauer, better known for the film adaptation by Penn (2007). The central theme addressed in our analysis will be abandonment, expressed in various ways by Chris, the protagonist: abandonment of relationships, abandonment of possessions, abandonment of oneself to the rhythms of nature. The third work is Lake Success: A Novel by Gary Shteyngart, in which we revisit and explore the “wisdom of doing”, of building, which is already introduced in Krakauer's novel. Finally, the acceptance of ruthless truth and the “sublime banality of existence”, which is revealed at the end of the journey and is also present in all the authors mentioned above, is at the centre of the last novel, Butcher's Crossing by John Williams. In the background of our work, as it couldn't be otherwise, is Thoreau, who offers the concepts through which it is possible to analyze the themes addressed by the different authors here considered, and with whom each of them, in one way or another, comes to terms.
Keywords: wilderness; journey; XIXth century literature; rebellion